Introduction to configural frequency analysis the search for types and antitypes in cross-classifications - Eye, Alexander von (Cambridge University Press, 1990)
Configural Frequency Analysis (CFA) is a method for analysis of groups of individuals in cross-classifications. Individuals belong to a type if their particular pattern of characteristics occurs more often than expected, and to an antityte if their particular pattern of characteristics occurs less often than expected. The author's original contribution is his linking of CFA to log-linear modeling and the General Linear Model, enabling the reader to relate CFA to a well-known statistical background. It is shown that CFA and log-linear modeling are methods that complement each other. Introduction to Configural Frequency Analysis covers the latest developments in CFA, and it will be easy to read even for those with only an elementary statistics course as a background
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Psychometrics; Discriminant analysis; Psychometrie; Konfigurationsfrequenzanalyse; Einführung